Johann Wilhelm von Archenholtz’s England und Italien (1785) and its British Travellee-Rewriters - Tarkka, Laura (United Kingdom, 2025)
This article examines the reception and translation of the first part of Johann Wilhelm von Archenholtz’s (1741-1812) England und Italien (Leipzig 1785) in Britain. First entering the British public sphere in French translation just before the French Revolution, the work also appeared in two English translations, A Picture of England (London 1789) and A View of the British Constitution (Edinburgh 1794), the latter of which was later reprinted as A Picture of England (London 1797). While Archenholtz’s work is known as a prime example of German Anglophilia, the article argues that the reactions of its British translators and reviewers – who are here conceptualised as “travellee-rewriters” – show that contemporary interpretations of Archenholtz’s political message merit closer attention. As these reactions show, Archenholtz’s England provided British subjects with a textual space in which to deliberate how their kingdom’s constitution related to republicanism and the notion of the “free state”.